Sensing mechanism of an optimized room temperature optical hydrogen gas sensor made of zinc oxide thin films - Mustaffa, Siti Nor Aliffah; Ariffin, Nurul Assikin; Khalaf, Ahmed Lateef; Yaacob, Mohd. Hanif; Tamchek, Nizam; Paiman, Suriati; Sagadevan, Suresh (Elsevier Editora, 2020)
Using the radiofrequency (RF) magnetron sputtering method, zinc oxide (ZnO) thin films were optimized for the optical hydrogen gas sensor at 27 °C. To generate optically controlled thin films, the following parameters have been optimized: argon/oxygen (Ar/O2), RF power, gas concentration and deposition time. As a result, ZnO thin films optimized at 4 % of O2, 150 W RF and 180 min gas concentration. This work focused on the effect of deposition parameters that included deposition time, RF power, argon/oxygen (Ar/O2) gas percentage, and annealing condition on thin-film thickness, surface roughness, crystal phase, phonon modes, and optical bandgap. From the physical characterization, we found that the formed product is crystalline in nature (powdered XRD) and Attenuated Total Reflection Fourier-Transform Infrared Spectroscopy (ATR-FTIR) analysis provided the surface functionality and bonding, while the UV–vis spectroscopy for the optical properties. AFM images show that the surface roughness is varying from 18.9 to 89.83 nm. The gas sensing mechanism of the RF-sputtered ZnO thin film was based on the surface reaction between adsorbed oxygen and the H2 gas where more oxygen was chemisorbed in the form of O2−, O−, and O2- by ZnO thin film. The calculated molar absorptivity, ε increased with the increase of RMS surface roughness whereby relatively high surface roughness is better to optically absorb H2 gas.